Monitoring human mesenchymal stromal cell differentiation by electrochemical impedance sensing - Angstmann, Michael; Brinkmann, Irena; Bieback, Karen; Breitkreutz, Dirk; Maercker, Christian (Cytotherapy, 2011)
Background aims - For their wide mesodermal differentiation potential, mesenchymal stromal/stem cells (MSC) are attractive candidates for tissue engineering. However, standardized quality control assays monitoring differentiation that are non-invasive and continuous over time are lacking. - Methods - We employed a non-invasive assay, using two different systems, to discriminate osteogenic and adipogenic differentiation of MSC by monitoring impedance. Fibroblasts and keratinocytes served as non-specific controls. Impedance profiles were recorded comparing MSC from bone marrow and adipose tissue, either non-induced or induced for osteogenesis or adipogenesis, for 5-14 days, and correlated with differentiation markers assessed by reverse transcription-quantitative polymerase chain reaction and Western blot. Additionally, differentiation modulating effects of extracellular matrix components were analyzed. - Results - Adhesion and growth-related impedance profiles of non-induced MSC roughly resembled those of fibroblasts, whereas keratinocytes differed significantly. Distinct from that, osteogenic induction of MSC revealed initially rapid and continuously rising impedance, corresponding to mineralized calcium matrix formation. Conversely, adipogenic induction caused shallower initial slopes and eventually declining profiles, corresponding to more compact, adipocyte-like cells with numerous lipid vacuoles. Pre-coating with either collagen type I or IV apparently favored osteogenesis and fibronectin adipogenesis. Impedance recordings correlated well with the extent of differentiation evaluated by histochemical staining and protein and gene expression. - Conclusions - Overall, our data demonstrate that impedance profiling offers a basis for standardized real-time, non-invasive high-throughput screening of MSC properties. It enables further testing of the influence of diffusible factors or extracellular matrix composites on MSC differentiation or maintenance of stemness, thus substantiating therapeutic application.